CAUSES AND SOLUTION TO REDUCE UNEMPLOYMENT VOCATIONAL SCHOOL GRADUATE IN INDONESIA - Nur Anita Yunikawati; Putra Hilmi Prayitno; Magistyo P Purboyo; Ni’matul Istiqomah; Emma Yunika Puspasari (UPT Penerbitan Universitas Jember)
This study aims to determine the causes and ways to provide solutions to reduce unemployment of vocational graduate students. The method used in this study using qualitative methods of descriptive. Data collection comes from primary data and secondary data. Primary data from this research comes from interviews with respondents is (unemployed graduate vocational students, vocational students who have not graduated, classroom teachers, parents of vocational students, employers, education offices). While secondary data obtained from documents related to the research. From this research found that SMK graduates are the biggest contributor to unemployment in Indonesia from year to year. The cause of SMK graduate students is difficult to accept work is a skill that is not in accordance with the needs of job seekers, vocational graduate students only competent one field, the curriculum used in SMK only print workers, not entrepreneurship, and the increasingly mushrooming SMK with a uniform major. There are two ways to reduce unemployment, the first is by promoting a creative economy with local wisdom and with strengthening and synergy between government, school, and industry in accordance with Triple Helix theory.